Analysis Of The Effect Of Organic Fertiliser Use On Plant And Soil Quality - Warmanti Mildaryani (Agriculture Journal, 2024)
Modern agriculture faces a major challenge in maintaining high productivity while preserving the environment. In recent decades, the use of synthetic chemical fertilisers has become a common practice worldwide to increase crop yields (Sari, 2023). This research aims at analysing the effect of organic fertiliser use on plant and soil quality. This research uses a quantitative method with a field experimental approach. This approach was chosen because it allows researchers to directly measure the effect of organic fertiliser use on soil quality and plants under environmental conditions. From the results in table 3 regarding the effect of granular and bulk organic fertilisers on plant growth, it shows that the NPK treatment alone produces the highest plant height (33.6 cm) with a production of 17.7 t/ha. In Table 4 regarding the effect of fertiliser treatment on dry weight and stem varieties, the combination of NPK with NPK + 2 t POG organic fertiliser gave a dry weight of grain of 19.5 kg and a dry weight of straw of 21.5 kg. From the results shown in Table 3, it can be seen that the use of bulk (PO bulk) and granular (POG) organic fertiliser has a positive effect on plant growth compared to the control. In Table 4, the combination of NPK with 2 tonnes of straw or granulated organic fertiliser (POG) resulted in an increase in grain dry weight, especially in the NPK + 2 t POG treatment, which reached 19.5 kg dry weight. From the results of this study, it is clear that the use of organic fertilisers significantly improves soil fertility and crop yields, especially when combined with chemical fertilisers such as NPK. Organic fertilisers not only improve soil physical and biological properties, but also increase the effectiveness of chemical fertilisers.